Distribution of macronutrients (N, P, K, Mg) from single-nutrient and compound fertilizers application in oil palm seedlings (Elaeis guineensis Jacq.) - Eko Noviandi Ginting; Suroso Rahutomo; Rana Farrasati; Iput Pradiko (Jurnal Ilmu Pertanian, 2021)
Nutrients availability and plant's ability to absorb nutrients are essential factors in supporting plant performance. There are two forms of fertilizer as a source of nutrients for oil palm, which are single-nutrient fertilizer (SNF) and briquette compound-nutrient fertilizer (BCNF). This study observed the concentration, uptake, distribution, and efficiency of macronutrients in plant organs of oil palm seedlings with two different fertilizer types. An experiment using oil palm seedlings was arranged in non-factorial complete randomized design (CRD) with three treatments, namely control, NPK in the form of briquettes, and single nutrient fertilizer consisting of urea, TSP, MOP, and kieserite with doses adjusting the composition of the slow-release BCNF (16-10-24-0.75) in three replications with a total of 27 seedlings. The results showed that the concentration, uptake, and distribution of nutrients between treatments and control were not significantly different. The order of nutrient uptake in leaves and stems of plants was N > K > Mg and P, while in roots was K > N > Mg > P. In BCNF and SNF treatments, the biomass accumulation in the stems, roots, and leaves were at percentage of 41 %, 30 %, and 29 %, while in the control, the biomass accumulation in the roots, stems, and leaves were at percentage of 39 %, 33 %, and 28 %, respectively. BCNF treatment had a greater efficiency indicated by a higher nutrient use efficiency (NUE) value compared to SNF or control.